Implementation of Pillantrophy to Improve the Identity of the Community of Kampung Pos RW 10 Kelurahan Pakansari, Cibinong District in the Pandemic - Muhamad Subkhan; Pat Kurniati (UIN Sunan Gunung Djati Bandung, 2021)
Philanthropy implementation is an attitude shown by the community through concrete actions in the form of mutual care as evidenced by sharing with others, helping each other when neighbors experience difficulties and difficulties by helping voluntarily without coercion and fostering good relations between each other. Community identity is an activity carried out by the community continuously and from generation to generation which is characterized by a close relationship between fellow members of the community, mutual cooperation or cooperation, mutual care and mutual empathy. The method used in collecting research data was purposive random sampling and the use of questionnaires. Questionnaire data obtained will be processed using descriptive analysis through statistical tests. The results of this study illustrate the implementation of an activity, namely philanthropy in a community environment. How can philanthropic activities still be carried out in a pandemic condition so that this activity has become a characteristic or identity of a community, this identity is a manifestation of the values of Pancasila which should continue to be preserved, not only in the RW 010 Pos Kampun but also throughout the nation and state in Indonesia.